2021
DOI: 10.1093/ckj/sfab029
|View full text |Cite
|
Sign up to set email alerts
|

Adverse clinical outcomes associated with RAAS inhibitor discontinuation: analysis of over 400000 patients from the UK Clinical Practice Research Datalink (CPRD)

Abstract: Background Users of guideline-recommended renin-angiotensin-aldosterone system (RAAS) inhibitors may experience disruptions to their treatment, for example due to hyperkalaemia, hypotension or acute kidney injury. The risks associated with treatment disruption have not been comprehensively assessed; therefore, we evaluated the risk of adverse clinical outcomes in RAAS inhibitor users experiencing treatment disruptions in a large population-wide database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Most prior studies have reported increased cardiovascular events following RAASi discontinuation [1215, 17]. In contrast, our study did not find differences in cardiovascular outcomes associated with RAASi discontinuation, similar to the report from Hundemer et al [16] Again, it is important to note that our population did not include patients with prior heart failure hospitalizations and was not limited to patients with proteinuria.…”
Section: Discussionsupporting
confidence: 87%
“…Most prior studies have reported increased cardiovascular events following RAASi discontinuation [1215, 17]. In contrast, our study did not find differences in cardiovascular outcomes associated with RAASi discontinuation, similar to the report from Hundemer et al [16] Again, it is important to note that our population did not include patients with prior heart failure hospitalizations and was not limited to patients with proteinuria.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, RAASi therapy is frequently downtitrated or discontinued in patients who experience hyperkalaemia, contributing to significant discrepancies between guideline recommendations and real-world practice regarding RAASi treatment [13][14][15][16]. Failure to achieve guideline-recommended doses of RAASi has been associated with adverse outcomes [8, 13,17]. Thus, there is an established need for safe and effective treatment of hyperkalaemia, in particular to permit maintenance of RAASi therapy.…”
Section: Open Accessmentioning
confidence: 99%
“…Recent KDIGO guidance on hyperkalaemia management in kidney disease highlighted that evidence supporting low-potassium diet is weak and that it may deprive patients of the benefits of a plant-rich diet [1]. Similarly, downtitration or discontinuation of RAASi deprives patients of the benefits of RAAS inhibition and is associated with an increased risk of adverse outcomes [8, 13,17]. The evidence for the efficacy of SPS/CPS is modest; one small, short-term, singleblinded RCT has been published comparing SPS to CPS, [34] however no comparison with placebo was performed and no studies have evaluated longer term efficacy or safety.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Third, these results were generated from well-designed trials involving experienced investigators who were encouraged to continue guideline-directed background care wherever possible, and thus, persistent use of RAS blockade was high. Whether these findings translate into more pronounced effects on RAS blockade discontinuation in real-world settings—where this occurs much more frequently than in clinical trials 27,28 —should be examined in future work, leveraging routinely collected data.…”
Section: Discussionmentioning
confidence: 99%